Exploring Green Banking Performance of Islamic Banks in Indonesia - Widiyanti, Dwi Retno; Hanifah, Sarah Hana; Supriani, Indri (International Journal of Islamic Economics and Finance (IJIEF), 2025)
The sustainable movement in the financial sector, known as green banking, has emerged as a global standard that obligates the financial industry to adhere to social and environmental responsibilities. Indonesian Islamic banks' green banking initiatives are examined in this study. Green Banking Disclosure Index (GBDI) indicators for 13 Islamic commercial banks were collected from their five-year sustainability reports. Bose et al. (2018)'s 21 GDBI indicators were thoroughly analyzed. Jeucken's typology measurement showed banks' four-stage movement from defensive and preventative to aggressive and "sustainable" in 2004. Jeucken's Typology of Banking and Sustainable Development functioned as the assessment framework for evaluating green banking performance. Among the 13 Islamic banks analysed, only six have chosen to publicly disclose their sustainability reports. The banks in question include Panin Dubai Syariah Bank, Muamalat Bank, Aladin Syariah Bank, Aceh Bank, BTPN Syariah Bank, and Mega Syariah Bank. The data reveals that no Islamic banks have reached the "sustainable" stage. Currently, two out of six Islamic banks are positioned in the offensive stage, while the other four are in the preventive stage. It can be posited that these financial institutions have commenced the shift towards a "sustainable" phase. The findings of this study on disclosure indicators in green banking indicate that Indonesian Islamic banks must revise their reporting methods concerning environmentally friendly banking practices. Moreover, considering their crucial role in advancing green banking in relation to sustainable development, Indonesian Islamic banks need to enhance the quality of their publicly accessible sustainability reports.